ПОДАТОК НА НЕРУХОМЕ МАЙНО, ВІДМІННЕ ВІД ЗЕМЕЛЬНОЇ ДІЛЯНКИ, ЯК МОЖЛИВІСТЬ ПОПОВНЕННЯ МІСЦЕВИХ БЮДЖЕТІВ - Gosteva, O.Yu. (V. Mamutov Institute of Economic and Legal Research of the National Academy of Sciences of Ukraine, 2015)
The components of the tax on real property other than land, as defined in the Tax Code of Ukraine, analyzed the experience of foreign countries in the field of real property taxation identified by its ability to adapt elements to domestic conditions. REFERENCES